2017
DOI: 10.1161/hypertensionaha.117.09262
|View full text |Cite
|
Sign up to set email alerts
|

P2y12 Receptor Promotes Pressure Overload–Induced Cardiac Remodeling via Platelet-Driven Inflammation in Mice

Abstract: Inflammation plays a critical role in adverse cardiac remodeling and heart failure. The P2y12 receptor is one of the predominant activating receptors for platelets, thus initiating inflammatory responses under various diseases. In this study, we investigated the functional significance of P2y12-mediated platelet activation in pressure overload-induced cardiac remodeling. Notably, P2y12 knockout (P2y12) mice exhibited suppressed transverse aortic constriction-induced changes in cardiac hypertrophy, collagen syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…In addition to local fibroblast activation, platelet-derived proteins ( 33 ), including TGF-β1 ( 19 ), contribute to the onset and progression of fibrosis. Platelet inhibition or depletion attenuates cardiac remodeling after myocardial infarction ( 48 , 49 ) or in response to pressure overload ( 18 , 33 ). We have previously demonstrated that miR-21 is abundant in platelets and miR-21 plasma levels are decreased by antiplatelet therapy ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to local fibroblast activation, platelet-derived proteins ( 33 ), including TGF-β1 ( 19 ), contribute to the onset and progression of fibrosis. Platelet inhibition or depletion attenuates cardiac remodeling after myocardial infarction ( 48 , 49 ) or in response to pressure overload ( 18 , 33 ). We have previously demonstrated that miR-21 is abundant in platelets and miR-21 plasma levels are decreased by antiplatelet therapy ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cardiomyocytes and CFs, high TGF-β1 levels are also found in blood platelets, where its release is controlled by Wiskott-Aldrich syndrome protein (WASp) ( 17 ). The platelet releasate is supposed to be a key driver of the inflammatory response in cardiac remodeling ( 18 ). It has been suggested that extravasated platelets are a major source of TGF-β1 in the myocardium upon cardiac injury ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanism by which SMYAD mediates its anti-hypertrophic effects remains unclear, and the signaling pathways that interact to drive hypertrophy are very complicated. To understand the molecular mechanisms responsible for SMYAD’s effects in HF, we investigated platelet, which has been shown to be activated in TAC-treated mice to induce cardiomyocyte hypertrophy and collagen synthesis (Wu et al, 2017a). We observed increased activation of cardiac CD41/61 and P-selectin in TAC-treated mice, as well as the reverse effect of SMYAD.…”
Section: Discussionmentioning
confidence: 99%
“…11-HETE and four kinds of EETs were purchased from Cayman Chemical (Ann Arbor, Michigan, USA). For the purchasing information on some of the other conventional reagents in our lab, please refer to our previous articles [15, 20, 21].…”
Section: Methodsmentioning
confidence: 99%